LIFE CYCLE, HABITS AND NATURAL ENEMIES OF Dichomeris famulata Meyrick (LEPIDOPTERA: GELECHIIDAE), PEST OF SORGO PANOJA IN THE CAUCA VALLEY - CIRO-R., LUZ DARY; MATALLANA-S., VICTORIA E.; PULIDO-F., JAIME I.; ZULUAGA-C., JOSÉ I. (Revista Colombiana de Entomología, 1992)
In the Cauca Valley (Colombia) Dichomeris famulata Meyrick (Lepidoptera: Gelechiidae) is actually one of the main pests affecting sorghum due to its high infestation levels, the damage caused, and its difficult control. An investigation was undertaken at the ICA's Centro de Investigaciones "Palmira" at Palmira (Valle) located at 1000 ma.s.l., 24°C of temperature and 74% of relative humidity, in order to study the life cycle, the habits, and the natural enemies, both under laboratory and field conditions. Under laboratory conditions, the lite cycle was: egg, 4 days; larva, 21.3 days; pupa, 6 days; female adult, 42.43 days; and mate adult, 38.3 days. The larval stage presented five instars. Female adults oviposited 129.31 eggs in 13.12 days. Maximum oviposition was observed on the fifth and sixth days alter the oviposition was initiated. The average infestation was 42 larvae per sorghum panicle. As a natural enemy in the field was detected Apsylophrys sp. (Hymenoptera: Encyrtidae) with 16% of parasitism. Under laboratory conditions, Trichogramma pretiosum Riley parasitized 60% of the eggs of D. famulata. Other natural enemies were the egg predator Chrysopa sp. and the pathogen Nomuraea rileyi (Farlow) Samson. D. famulata was also detected feeding on Amaranthus dubius Mart. and Zea mays L.